2011
DOI: 10.3109/00016357.2011.572287
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of two different collar implant structures on stress distribution under cantilever fixed partial dentures

Abstract: It has been concluded that stress distribution in implant-supported CFPDs correlated with the macro design of the implant collar and the direction of applied force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The prognosis and long-term success of dental implant treatment are greatly influenced by the biomechanical environment in which they are exposed [6], in combination with the physical and geometric properties of each implant component [7]; the clinician's poor knowledge of biomechanical concepts is related to the failure of implant restorations [8]. Clinicians should know that the process and consequences of stress transmission to the surrounding bone depends on the nature of the applied load (the amplitude, direction and frequency), the implant design, the biological and biomechanical properties of the bone-implant interface and the bone tissue reaction to the mechanical environment created by the load over the implant [9].…”
Section: Biomechanics In Implantologymentioning
confidence: 99%
“…The prognosis and long-term success of dental implant treatment are greatly influenced by the biomechanical environment in which they are exposed [6], in combination with the physical and geometric properties of each implant component [7]; the clinician's poor knowledge of biomechanical concepts is related to the failure of implant restorations [8]. Clinicians should know that the process and consequences of stress transmission to the surrounding bone depends on the nature of the applied load (the amplitude, direction and frequency), the implant design, the biological and biomechanical properties of the bone-implant interface and the bone tissue reaction to the mechanical environment created by the load over the implant [9].…”
Section: Biomechanics In Implantologymentioning
confidence: 99%
“…In addition, it has been concluded that stress distribution in implant-supported CFPDs correlated with the macro design of the implant collar. Meriç, et al showed that stresses at the veneering material decreased with microthreaded collar implant design [13].…”
Section: Implant Characteristicsmentioning
confidence: 99%
“…The behavior of each element is described by a set of equations, and the solution of the entire system is obtained by combining the solutions of all elements. FEM has been successfully applied to simulate the behavior of various biomaterials, including dental implants, hip prostheses, and spinal implants [ 15 , 16 , 17 ]. To overcome the toxicity issues associated with conventional biocompatible alloys, various alloys have been developed in recent years.…”
Section: Introductionmentioning
confidence: 99%